from a handpicked tutor in LIVE 1-to-1 classes

# Find the product

(i) (a^{2} ) × (2a^{22} ) × (4a^{26}) (ii) (2/3 xy) × (-9/10 x^{2} y^{2})

(iii) (-10/3 pq^{3} ) × (6/5 p^{3}q) (iv) x × x^{2 }× x^{3 }× x^{4}

**Solution:**

Multiplication of two algebraic expressions or variable expressions involves multiplying two expressions that are combined with arithmetic operations such as addition, subtraction, multiplication, division, and contain constants, variables, terms, and coefficients.

(i) (a^{2} ) × (2a^{22} ) × (4a^{26} ) = 2 × 4 × a^{2 }× a^{22} × a^{26} = 8a^{50} [According to exponent rules, a^{m} × a^{n} = a^{m + n}]

(ii) (2/3 xy) × ( -9/10 x^{2} y^{2} ) = (2/3) × (-9/10) × x × y × x^{2} × y^{2} = -3/5 x^{3} y^{3} [Since, a^{m} × a^{n} = a^{m + n}]

(iii) (-10/3 pq^{3}) × (6/5 p^{3}q) = -10/3 × 6/5 × p × q^{3} × p^{3 }× q = - 4 p^{4}q^{4} [Since, a^{m} × a^{n} = a^{m + n}]

(iv) x × x^{2 }× x^{3} × x^{4} = x^{10 }[Since, a^{m} × a^{n} = a^{m + n}]

**☛ Check: **NCERT Solutions for Class 8 Maths Chapter 9

**Video Solution:**

## Find the product. (i) (a² ) × (2a²² ) × (4a²⁶) (ii) (2/3 xy) × (-9/10 x² y²) (iii) (-10/3 pq³ ) × (6/5 p³q) (iv) x × x²^{ }× x³^{ }× x⁴

NCERT Solutions Class 8 Maths Chapter 9 Exercise 9.3 Question 3

**Summary:**

The product of the following expressions: (i) (a^{2} ) × (2a^{22} ) × (4a^{26}) (ii) (2/3 xy) × (-9/10 x^{2} y^{2}) (iii) (-10/3 pq^{3} ) × (6/5 p^{3}q) (iv) x × x^{2 }× x^{3 }× x^{4} are: (i) 8a^{50}, (ii) -3/5 x^{3} y^{3}, (iii) - 4 p^{4}q^{4}, (iv) x^{10}

**☛ Related Questions:**

- Carry out the multiplication of the expressions in each of the following pairs. (i) 4 p, q + r (ii) ab, a - b (iii) a + b, 7a2b2 (iv) a2 - 9, 4a (v) pq + qr + rp, 0
- Complete the table.
- (a) Simplify 3x(4x - 5) + 3 and find its values for (i) x = 3 (ii) x = 1/2 (b) Simplify a (a2 + a + 1)+ 5 and find its values for (i) a = 0, (ii) a =1, (iii) a = - 1
- (a) Add: p( p - q), q(q - r ) and r (r - p) (b) Add: 2x (z - x - y) and 2y(z- y - x) (c) Subtract: 3l (l - 4m + 5n) from 4l (10n - 3m + 2l ) (d) Subtract: 3a(a + b + c) - 2b(a - b + c) from 4c (-a + b + c)

visual curriculum